(untitled) (Sebha University Conference Proceedings, 2025)
This research is a study and design of a stand-alone solar energy system for a tourist hotel in the Libyan desert in an area called Abu Njeim Hotel, the problem facing tourists in that rugged desert that is no public electricity network nearby. Many tourists have their cars were broken down and they get lost in the desert. So far, there is no hotel or a small rest house in this area, due to the inability to provide an electric energy source. This case was studied to provide a safe place for people and tourists to rest, to solve this problem: It was proposed to design a stand-alone solar energy system to provide this hotel with electricity throughout the day. This research has studied all information about the site and its meteorological data. The main components of this system are solar panels, inverters, charge controllers, and batteries. The electrical load of this hotel, as well as the percentage of solar radiation on-site, was calculated. PVSyst software was used to scale and analysis the data for this system. This study contributes to finding a solution for operating a tourist hotel in the Libyan desert in terms of design and sizing. These results can be benefited from in other sites by following the same steps that were used in this paper.